JAMINAN KEBEBASAN PERS DI INDONESIA - Agustini, Sri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Guaranteed press freedom in Indonesia is mentioned in the constitution, which states that independence expresses thoughts and opinions (HAM) in Indonesia guaranteed in Article 28 which states that freedom of association and assembly issues thoughts with oral and written and so forth stipulated by law. Article 28 F states that everyone has the right to communicate and obtain information to develop their personal and social environment, and has the right to seek, obtain, possess, store, process and convey information using all types of available channels. The freedom of the press that occurred in the reform era was structural freedom along with the change in the system of government. The change in the system of government, is more or less influenced by the flow of globalization, so that the Indonesian press in this era tended to adhere to Libertarianism.